Integrated Project as Innovative Assessment to Enhance Learning Experience in Thermodynamics Class - Nonni Soraya Sambudi; Raihan Mahirah Ramli (Universitas Pendidikan Indonesia (UPI), 2021)
An integrated project is introduced to students to relate the concepts and equations taught between courses in the same semester. It also helps students in managing allocated time for assessments and collaborating among them, which eventually enhances their learning experience, especially for thermodynamics courses. In this case, the integrated project was done by relating two courses: Chemical Engineering Thermodynamics 2 and Separation Process 1 for Year 2 students. The methanol production plant was chosen as a model case, where students need to simulate the vapor/liquid equilibrium in the purification unit using HYSYS simulation software. Overall, students show highly positive sentiments upon the projects, in which more than 90% of them think that the project helps them to understand the coursework materials and prepare for other assessments. The majority of students want to experience the same type of project in the future, and it helps to save their time rather than working on separate projects. The project also exposes the students to set skills related to technical competence and soft skills that could build their characters.